2020
DOI: 10.5194/angeo-38-527-2020
|View full text |Cite
|
Sign up to set email alerts
|

Forcing mechanisms of the migrating quarterdiurnal tide

Abstract: Abstract. We used a nonlinear mechanistic global circulation model to analyze the migrating quarterdiurnal tide (QDT) in the middle atmosphere with focus on its possible forcing mechanisms: the absorption of solar radiation by ozone and water vapor, nonlinear tidal interactions, and gravity wave–tide interactions. We show a climatology of the QDT amplitudes, and we examine the contribution of the different forcing mechanisms to the QDT amplitude. To this end, we first extracted the QDT from the model tendency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Secondary sources, such as nonlinear tide-tide interactions and gravity wave-tide interactions, can also play a role. Geißler et al (2020) have used the same GCM to study the forcing mechanisms of the migrating quarterdiurnal tide (QDT). Among the studied mechanisms were the absorption of solar radiation by ozone and water vapor, nonlinear tidal interactions, and gravity wave-tide interactions.…”
Section: Modeling Of Vertical Coupling By Wavesmentioning
confidence: 99%
“…Secondary sources, such as nonlinear tide-tide interactions and gravity wave-tide interactions, can also play a role. Geißler et al (2020) have used the same GCM to study the forcing mechanisms of the migrating quarterdiurnal tide (QDT). Among the studied mechanisms were the absorption of solar radiation by ozone and water vapor, nonlinear tidal interactions, and gravity wave-tide interactions.…”
Section: Modeling Of Vertical Coupling By Wavesmentioning
confidence: 99%
“…Despite receiving less attention in comparison to the lower‐order migrating tides, QW4 is a persistent feature in the mesosphere and lower thermosphere and is characterized by its long vertical wavelengths, which allow it to propagate to higher altitudes. The major forcing mechanism of QW4 is the absorption of solar radiation by ozone in the stratosphere (GeiBler et al., 2020; Xu et al., 2012). It should be noted that QW4 has a weaker amplitude than the lower‐order migrating tides with s = 1, s = 2, and s = 3 (M. Liu et al., 2015; Azeem et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Model diagnostics indicate that the non-linear tidal interactions contribute to the generation of the quaddiurnal tides (e.g., Smith et al, 2004). However, Geißler et al (2020) found through numerical experiments that solar forcing is the most important mechanism in generating quaddiurnal tides in the MLT region, and non-linear interactions and gravity waves can be important during September equinox conditions. Not much is known about the quaddiurnal tide in the upper thermosphere.…”
Section: Introductionmentioning
confidence: 99%